Matematică
mihaidarie76
2015-11-11 17:21:30
(2x+3)×1,(3)=(3 1/3) la patrat
Răspunsuri la întrebare
florentinracovi
2015-11-11 22:25:31

[latex](2x+3)cdotfrac{13-1}{9}=(frac{3cdot3+1}{3})^2\ Rightarrow;frac{(2x+3)cdot4}{3}=frac{100}{9}\ adica:;3cdot(2x+3)cdot4=100;\}} de;unde;24x+36=100;deci;;x=frac{64^{(8}}{24}=frac{8}{3}[/latex]

robertobix
2015-11-11 22:26:46

(2x+3)×1,(3)=(3 1/3)^2 1,(3) = (13-1)/9 = 12/9 = 4/3 3 1/3 = (3×3+1)/3 = 10/3 (2X+3) × 4/3 = (10/3)^2 (2X+3)×4/3 = 100/9 |×9 12(2X+3) = 100 2X+3 = 100/12 2X+3 = 25/3 2X = 25/3 - 3 2X = 25/3 - 9/3 2X = 16/3 X = 16/3 × 1/2 X = 16/6 X = 8/3

Adăugați un răspuns